Honeybees: that build perfect combs - Yahya, Harun (Goodword Books New Delhi, 2005)
"Honeybees: That Build Perfect Combs" is an engaging exploration of the remarkable lives of honeybees and their extraordinary ability to construct intricate honeycombs. The book details the biology and social structure of honeybee colonies, explaining how these insects work together harmoniously to create their hexagonal wax cells, which serve as storage for honey and pollen and as nurseries for their young. Through vibrant illustrations and accessible language, the text highlights the importance of honeybees in pollination and their critical role in maintaining healthy ecosystems. This work aims to inspire appreciation for these industrious creatures and raise awareness about their conservation.